HOW CAPITAL GOODS FIRMS UPGRADE INNOVATION CAPACITY: A CASE STUDY - Aminullah, Erman; Prihadyanti, Dian; Nadhiroh, Irene Muflikh; Laksani, Chichi Shintia (Pusat Penelitian Perkembangan Iptek, LIPI, 2014)
Objective of the research is to reveal how networks upgrade innovation capacity and to derive policy suggestions necessary for enhancing capa-bilities for process improvements and innovations, including interactions between users and producers in capital goods industry. The case study results showed that: i) the main driver of technological learning in the capital goods companies is the vision of top management; ii) product innovation as the improvement of existing product can be the results of informal learning without doing formal R&D activity; iii) the limited co-operative arrangements among producer, supplier and consultant are sufficient for stimulating lower level of innovations, which is new to the firma innovations - rather than new to the market; and iv) the pro-ducers-users interaction in the forms of exchange in goods and infor-mation as well as cooperation will contribute to stimulate innovation in companies. Knowledge sharing through innovation network has a central role in upgrading innovation capacity. It implies that the necessary poli-cies to intensify the wiring innovation network in capital goods industry are: i) the establishment of bridging institution or network broker for training, facilitating and mobilizing of network formation; ii) government financial assistance for hiring external experts/consultant to upgrade the innovation capacity of industry; iii) incentives (i.e.financial compensa-tion, recognition and career advancement) for university and research institute professors working to upgrade the innovation capacity of indus-try; and iv) government consultancy services and/or subsidized consul-tancy services from universities/research institutions to upgrade innova-tion capacity of industry.